In Vitro Digestibility Evaluation of Cotton Stalk Treated with Different Substrate Based Fiber Degrading Liquid Enzymes at Varying Duration - S. F. Nipane (Indian Journal of Animal Nutrition, 2024)
The present study was made to evaluate the effect of fiber degrading liquid enzymes solution at different dilutions and duration on in vitro dry matter digestibility of cotton stalk. The cotton stalk was treated with rice straw, untreated cotton stalk and ozone treated cotton stalk substrate based liquid fibrolytic enzymes with 4 lit/kg (2 lit of extracted enzyme and 2 lit of water per kg substrate) for 24, 48, 72 and 96 hr soaking period. Liquid fibrolytic enzymes extraction, purification, characterization and standardization, enzyme activity, and application dosage optimization for substrate was carried out in Department of Chemical Engineering, Visvesvaraya National Institute of Technology, Nagpur. The treated substrates with different dilutions and durations were in vitro incubated to ascertain their effect on digestibility. The results revealed significant differences (p